2019
DOI: 10.1016/j.midw.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Women's knowledge of maternal danger signs during pregnancy: Findings from a cross-sectional survey in Papua New Guinea

Abstract: Objective: to explore knowledge of pregnancy related danger signs among women attending antenatal clinics in Papua New Guinea. Design: cross-sectional survey undertaken as part of a wider integrated health and demographic survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 29 publications
5
26
0
4
Order By: Relevance
“…And, when one evaluated the right of universality in the access of women during pregnancy and the puerperium it was found that the federal policy on maternal and child health has weaknesses in access to care for women in prenatal care, childbirth and the puerperium, therefore a study recommended that managers prioritize actions to improve this policy to guarantee access to health of the binomial (20) . Similar results were found in researches that showed that women who received information on pregnancy and childbirth were significantly more likely to know any danger signs, compared to women who did not receive information (21) ; and identified a low level of women's knowledge about obstetric danger signs during pregnancy, childbirth and postpartum, finding that women who were unaware were more susceptible to delay in deciding to seek care. This can be explained due to the failure in communication between the healthcare team and the patient (22) .…”
Section: A Survey That Evaluated 3 Delays Model In Asupporting
confidence: 80%
“…And, when one evaluated the right of universality in the access of women during pregnancy and the puerperium it was found that the federal policy on maternal and child health has weaknesses in access to care for women in prenatal care, childbirth and the puerperium, therefore a study recommended that managers prioritize actions to improve this policy to guarantee access to health of the binomial (20) . Similar results were found in researches that showed that women who received information on pregnancy and childbirth were significantly more likely to know any danger signs, compared to women who did not receive information (21) ; and identified a low level of women's knowledge about obstetric danger signs during pregnancy, childbirth and postpartum, finding that women who were unaware were more susceptible to delay in deciding to seek care. This can be explained due to the failure in communication between the healthcare team and the patient (22) .…”
Section: A Survey That Evaluated 3 Delays Model In Asupporting
confidence: 80%
“…Studies in the past have equated women's knowledge on obstetric dangers signs with their ability to spontaneously recall varying number of danger signs [8][9][10][15][16][17][18]. These studies surveyed women in the community [8,9,16,18,19] at different times after their last pregnancy [8][9][10] and assessed danger signs by classifying them as related to antepartum-, intrapartum-and postpartum-period [9,15,16,19]. Though we cannot make direct comparisons of knowledge levels, the median number of danger signs recalled in our study is comparable to that reported elsewhere [8].…”
Section: Knowledge Of Obstetric Danger Signsmentioning
confidence: 99%
“…A pregnant woman's understanding of danger signs during pregnancy is vital to seeking timely care during obstetric emergencies and reducing the rst delay [2]. Other studies have assessed knowledge levels by women's ability to recall danger signs [7][8][9][10]. Although recall indicates that a woman has heard of danger signs, what action she would take if faced with emergency situations depends on her understanding of the danger signs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the past have equated women's knowledge on obstetric dangers signs with their ability to spontaneously recall varying number of danger signs [13][14][15][19][20][21][22]. These studies surveyed women in the community [13,14,20,22,23] at different times after their last pregnancy [13][14][15] and assessed danger signs by classifying them as related to antepartum-, intrapartum-and postpartum-period [14,19,20,23]. Though we cannot directly compare the levels of knowledge, the median number of danger signs recalled in our study is comparable to that reported elsewhere [13].…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the consequences of rst delay in seeking care during obstetric emergencies, a pregnant woman's knowledge and understanding of danger signs during pregnancy is vital in seeking timely care [2]. Studies in other settings have assessed knowledge by women's ability to recall danger signs [12][13][14][15]. Although recall indicates that a woman has heard of danger signs, what action she would take if faced with emergency situations depends on her understanding of the danger signs.…”
Section: Introductionmentioning
confidence: 99%